Techno economic analysis of microgrid with an efficient energy management system and inverter control strategies. (December 2021) - Sadees, M.; Roselyn, J. Preetha; Vijayakumar, K.; Ravi, Anirudhh
Abstract: A microgrid comprises of distributed energy resources with the capability of operating independently as an islanded mode or in a grid connected mode. The efficacy of a microgrid is based on the performance of the control strategy and the energy management strategy. Therefore, in this paper the feasibility of an efficient inverter control strategy and energy management strategy for microgrid are studied. The proposed microgridis implemented with master-slave energy management control and battery management system for effective power flow control in an islanded and grid connected mode. A three-layer hierarchical energy management strategy comprising of master-slave system to provide continuous supply at all conditions and effective switchover operations between grid connected and islanded modes of operation is proposed. The voltage-frequency control under standalone mode of operation and P-Q control using hysteresis current control under grid-connected mode of operation are developed and the system parameters like real power, reactive power and voltage at the PCC are analyzed after the implementation of proposed controllers under islanded and grid connected modes of operation. The proposed model achieves voltage and frequency regulation under varying system operating conditions. Also, a techno-economic analysis is performed in HOMER software where the cost of energy and return on investment are studied for the proposed microgrid system by which levelized cost and payback period is reduced. The proposed control algorithms are implemented through MATLAB simulation and tested in a real-time for 1 kW grid-connected solar PV system.